Life under milk wood : women workers in rubber plantations : an overview - Uyangoda, Jayadeva (Colombo, Sri Lanka : Women's Education and Research Centre, 1995)
Study conducted on Kalutara District in 1992.
Keywords: Women rubber industry workers -- Sri Lanka; Rubber plantation workers -- Sri Lanka